DIAGNOSTIC ACCURACY OF ULTRASOUND FOR SMALL BOWEL OBSTRUCTION: A SYSTEMATIC REVIEW - Tanjung, Yeriano (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
An obstruction of the small bowel, which can be caused by mechanical blockage of the bowel, is a prevalent medical emergency that requires surgical intervention. However, intra-abdominal adhesions are the leading cause of small intestine obstruction in industrialized countries. Obstruction of the small bowel can be caused by a wide variety of pathologic events; however, the most prevalent cause is intra-abdominal adhesions. Radiographs are routinely used as a supplementary imaging modality; however, ultrasonography is an imaging modality that is both more sensitive and more specific than radiographs. POCUS is an efficient approach for detecting dilated loops of intestine in patients whose diagnoses may be consistent with SBO. It is probable that employing POCUS may reduce the number of CT scans that are required in order to arrive at an appropriate diagnosis of SBO. This, in turn, will speed up the surgical management and care of patients in the emergency department. When evaluating these patients, however, it is important to exercise caution when interpreting negative ultrasound findings due to the fact that POCUS is less sensitive than other ultrasound techniques. According to the findings of recent studies, diagnostic ultrasound, particularly when performed using POCUS, has a high degree of accuracy. The sensitivity and negative predictive value of a US examination in determining SBO are practically both one hundred percent.